‘A room with a view’ Emphasizing experiences - Finstad, Helga Helland (The Journal of Practice Teaching and Learning, 2012)
This paper describes a study of how the phenomenon of reflection on experience contributes to development of practical knowledge. Reflection on experiences and reflective practice are frequent themes in research reports and within Health and Social Workers’ practice, as well as in different post-educational programmes in mentoring. Data were collected through two focus-group discussions with twelve mid-level leaders in Norway. In addition, the analysis was inspired by an interpretation drawing on hermeneutic phenomenology. The results show what a leader can adapt and learn from mentoring in a practical training programme, and how to use this mentoring to develop practical knowledge within the organisation. The study concluded that there is a need for mentoring in practice, a room for critical reflection on experience and practice within a health organization. Practitioners have to be critical and reflective on their judgment in action, or ethical dilemmas of clinical experiences that filter and mirror their practice.